Produktivitas Combined Terminal Trailer Bongkar Muat Petikemas di Teluk Lamong - Syerehan Maghriba Shalawatika; Darmawan Apriyadi; Aisyah Rahmawati (Institut Transportasi dan Logistik Trisakti, 2021)
PT Terminal Teluk Lamong is a subsidiary of Pelindo III which is an expansion of Tanjung Perak Port which is engaged in container services. The aim of this research is to analyze the effect of the availability and waiting time of a combined terminal trailer on the loading and unloading productivity of PT Terminal Teluk Lamong. The problem of this research is the inadequate number of combined terminal trailers, the occurrence of waiting trucks, inadequate number of combined terminal trailers, changes in location, weight of containers transported by CTT, the high level of damage to the combined terminal trailer, difficulty in spare parts or spare parts. The results showed that there was a significant effect between the availability and waiting time of CTT on loading and unloading productivity where the correlation coefficient test showed 0.848 which means that there is a very strong influence. Meanwhile, the correlation coefficient of determination test shows that the influence between the availability and waiting time of CTT and loading and unloading productivity is 71.9% while the remaining 28.1% is influenced by other factors.